The World Wide Lightning Location Network (WWLLN) over Spain - E. A. Navarro; E. A. Navarro; J. A. Portí; A. Salinas; S. Toledo-Redondo; J. Segura-García; A. Castilla; V. Montagud-Camps; I. Albert (Natural Hazards and Earth System Sciences)
The World Wide Lightning Location Network (WWLLN) operates a distributed network of stations which detect lightning signals at a planetary scale. Very high currents from lightning strokes radiate strong very low frequency signals in the 6–22 kHz band, which are detected up to 10 000 km away by the WWLLN stations and which are used to determine the time and position of the lightning stroke detected by triangulation, similarly to global positioning systems. Studies of the performance of the WWLLN in different areas around the world have already been reported in the literature, but similar studies for west European regions are still unavailable. This work presents a study to determine the detection efficiency and location accuracy of the WWLLN over Spain by comparing its data with those of the Spanish State Meteorological Agency, AEMET, during 2012 taken as the ground truth. The study provides a detection efficiency for the WWLLN of around 29 % and a location accuracy of between 2 and 3 km. The efficiency for high-energy strokes is considerably higher. A study of four subregions with different geographical features is also considered. The peak current distribution of lightning events in these regions is obtained, and a possible link to the WWLLN performance is discussed. Finally, an application of the WWLLN data for three major storms in 2020, 2021, and 2022 in the Mediterranean area of Spain demonstrates that the WWLLN is well suited for tracking the time evolution of adverse meteorological phenomena.